Blue Economy: Framework for Integrating Economic Growth with Marine Ecosystem - Ram Priye Kumar Sahu; Raviteja Doppalapudi (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
The Blue Economy is an economic framework that integrates economic growth with marine ecosystem sustainability, acknowledging the oceans as vital to global development. The concept gained prominence at the Rio+20 United Nations Conference on Sustainable Development in 2012, emphasizing the need for a sustainable ocean-based economy that balances economic opportunities with environmental conservation and social equity. It encompasses a wide range of sectors, including fisheries, aquaculture, maritime transport, marine biotechnology, renewable energy, and coastal tourism, all of which play a crucial role in global trade, food security, and employment generation. The objective of this paper is to examine the evolution, components, opportunities, and challenges of the Blue Economy while identifying pathways for its sustainable development. The study follows a qualitative approach by analysing existing literature, global policy frameworks, and case studies to evaluate the effectiveness of different ocean-based economic models. Findings indicate that while the Blue Economy presents immense potential for economic growth and employment, it faces several critical challenges, such as overfishing, habitat destruction, climate change impacts, and governance issues. The exploitation of non-living marine resources, such as deep-sea mining and offshore oil and gas extraction, also raises concerns about long-term ecological sustainability. To overcome these challenges, the paper highlights the importance of strong governance frameworks, investment in marine research and technology, and the development of policies that promote sustainable resource management. The role of marine protected areas, sustainable fishing practices, and advancements in renewable ocean energy is emphasized as key strategies for balancing economic benefits with environmental conservation. The private sector, in collaboration with governments and international organizations, must play a central role in driving sustainable investments and innovations. Ultimately, the Blue Economy has the potential to support long-term economic development while preserving marine biodiversity and improving the livelihoods of coastal communities. By adopting sustainable practices, enforcing regulations, and investing in science and data-driven decision-making, nations can harness ocean resources responsibly. This paper underscores the need for an integrated approach that aligns economic growth with environmental stewardship, ensuring that the benefits of ocean-based industries are equitably shared while safeguarding marine ecosystems for future generations.